El régimen sucesorio de las acciones - Auler Soto, Guillermo (2023)
The purpose of this article is to provide the reader with an understanding of how the transfer of shares in companies, especially in corporations, takes place once the original owner has passed away, i.e., the transfer of shares in the inheritance regime; as well as the different problems and risks that may arise due to the lack of regulation in commercial matters on this specific figure.For the analysis, reference is made to the different stages of the transfer and to other regulations that complement the legal solutions to these cases. Thus, the Civil Code and the different resolutions on registry area are analyzed, with the purpose of knowing the moment in which the heirs can effectively call themselves owners of the shares that correspond to them; this process goes through knowing the heirs of the estate of the deceased and subsequently, through the division and partition of the co-ownership that arises on the shares.